Transhumance across IGAD region - Kasimbu, Japheth (International Livestock Research Institute, 2022)
Presentation by Japheth Kasimbu on TRANSHUMANCE; the seasonal movement of pastoralists and their herds from their usual grazing land, mainly in search of water and pasture.